1987
DOI: 10.1007/bf01812853
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of mitochondrial disorders

Abstract: Mitochondrial disorders, namely defects of fatty acid oxidation, defects of pyruvate metabolism and defects of the respiratory chain are heterogenous in clinical picture and in response to therapeutic attempts. Defects of fatty acid metabolism are amenable to therapy by dietary means, carnitine substitution and in some cases with vitamins. Defects in pyruvate metabolism do not respond to therapy except in some special cases. Therapeutic attempts include dietary measures, vitamins as coenzyme precursors. Defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

1990
1990
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 38 publications
0
24
0
4
Order By: Relevance
“…After that, when the drugs are known to be safe (several of them are already tested in other patients), they can be tested on patients with defects in oxidative phosphorylation. Of course together with other treatments that proved valuable in individual patients [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…After that, when the drugs are known to be safe (several of them are already tested in other patients), they can be tested on patients with defects in oxidative phosphorylation. Of course together with other treatments that proved valuable in individual patients [20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results have been described in some patients with complex I deficiency (Wijburg et al, 1989) and complex III deficiency (Eleff et al, 1984) but in other patients no improvement was observed at all (Przyrembel, 1987).…”
Section: Resultsmentioning
confidence: 93%
“…If a bioenergetic defect underlies neurodegeneration in Parkinson's disease, therapeutic interventions which ameliorate or bypass the metabolic defect might have a protective effect (Beal, 1992;Przyrembel, 1987). Such approaches might include: i) vitamins such as thiamine, riboflavine and biotin which are coenzymes of respiratory chain enzymes; ii) compounds such as vitamin C or vitamin K3 (menadione) to bridge a defect in electron transport; iii) the use of coenzyme Q-10 as an electron acceptor or donor; and iv) N-acetyl carnitine which has the potential to shunt oxidative metabolism down stream from complex I.…”
Section: Mitochondrial Defectsmentioning
confidence: 99%